Reproductive Strategies in Mediterranean Legumes: Trade-Offs between Phenology, Seed Size and Vigor within and between Wild and Domesticated Lupinus Species Collected along Aridity Gradients - Berger, Jens D.; Shrestha, Damber; Ludwig, Christiane (Frontiers in Plant Science, 2017)
To investigate wild and domesticated Mediterranean annual reproductive strategies, common garden comparisons of Old World lupins collected along aridity gradients were initiated. These are excellent candidates for ecophysiology, being widely distributed across contrasting environments, having distinct domestication histories, from ancient L. albus to recently domesticated L. angustifolius and L. luteus, facilitating the study of both natural and human selection. Strong trade-offs between seed size, early vigour and phenology were observed: vigour increasing, and flowering becoming earlier with increasing seed size. Despite large specific differences in all these traits, natural and human selection have operated in very similar ways in all 3 species. In wild material, as collection environments became drier and hotter, phenology became earlier, while seed size, early vigour and reproductive investment increased. Wild and domesticated germplasm separated along similar lines. Within similar habitats, domesticated material was consistently earlier, with larger seeds, greater early vigour and higher reproductive investment than wild, suggesting selection for both early establishment and timely maturity/drought escape in both domesticated and wild low rainfall ecotypes. Species differences reflected their distribution. Small and soft-seeded, low vigour L. luteus had a late, rainfall-responsive phenology specifically adapted to long season environments, and a narrow coastal distribution. L. angustifolius was much more conservative; more hard-seeded, flowering and maturing much earlier, with a wide Mediterranean distribution. L. albus flowered earlier but matured much later, with longer reproductive phases supporting much larger seed sizes and early vigour than either L. luteus or L. angustifolius. This ruderal/competitive combination appears to give L. albus a broad adaptive capacity, reflected in its relatively wider Mediterranean/North African distribution.